POTENSI TEGAKAN HUTAN TEMBAWANG DI DESA SEHE LUSUR KECAMATAN KUALA BEHE KABUPATEN LANDAK - Setiawan, David Agus; Dewantara, Iswan; Lumangkun, Augustine (Universitas Tanjungpura, 2018)
The forest of Tembawang in the village of Sehe Lusur is quite extensive and usefull for the local community. However, information about potential stands in the Tembawang forest has not yet been known. Therefore, this research aimed to find out how was the potential forest in the Tembawang. This research used the Sistematic Strip Sampling method by away of cruissing 100 % and analyzed using the formula of the volume unit. The results showed that the total volume of the stands in this forest was 319,98 m³, it consisted of: 86,112 m³ for Dipterocarpaceae; 217,687 m³ for Non Dipterocarpaceae; 16,181 m³ for species protected (Eusideroxylon zwageri). The average of total volume per hectare was 54,791 m³/ha. Tree spesies which had the highest potential of stands total volume was Tengkawang (Shorea sp.) with volume 69,925 m³. Based on the growth level, there ware 53 tree/ha, 55 poles/ha, 85 sapling/ha and 75 seedling/ha. The sufficiency number potential of stems based on the standards of the Departemant Kehutanan in 1989 at the level of the tree was quite, while at the level of seedling, sapling and pole was still less.Keywords: Potential stands, Tembawang.